Understanding drivers of brand love - the role of personalized ads on social media. Issue 1 (25th November 2020) - Tran, Trang P.; Muldrow, Adrienne; Ho, Khanh Ngoc Bich
Abstract : Purpose: This paper aims to test a theory-driven model reflecting the effects of perceived personalization on consumer–brand relationships on social media. Design/methodology/approach: The conceptual model is empirically tested through two studies using partial least squares-structural equation modeling. Other techniques, such as common method bias, multigroup comparison, mediation analysis and model fit comparison, are also used to give more insights into the analytical process. Findings: Data from two studies show that perceived personalization is positively related to brand-related outcomes including brand self-expressiveness, consumer–brand engagement and brand connection. While consumer–brand engagement and brand connection are positively related to brand love, brand self-expressiveness is not. Research limitations/implications: The paper contributes to the advertising and brand management literature by shedding light on a better understanding of the impact of personalization in the digital world. Practical implications: Management could learn important lessons from personalization. If a strategy of promoting personalized ads is implemented successfully, those ads could change customer perceptions of brands which ultimately strengthens brand love. Originality/value: This research provides an empirical model that helps marketers better understand the factors affecting brand love with personalized ads on social media.